2019
DOI: 10.3727/096504018x15179668157803
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of NADPH Oxidase 4 Attenuates Hypoxia Resistance in Neuroblastoma Cells SH-SY5Y by Inhibiting PI3K/Akt-Dependent Glycolysis

Abstract: Hypoxia-induced chemoresistance is a major obstacle in the development of effective cancer therapy. In our study, the reversal abilities of NADPH oxidase 4 (NOX4) silence on the hypoxia resistance and the potential mechanism were investigated. Our data showed that the expression of NOX4 was up-regulated in human neuroblastoma cells SHSY-5Y under hypoxia condition time-dependently. Knockdown of NOX4 expression by siRNA inhibited glycolysis induced by hypoxia through decreasing the expression of glycolysis relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In this study, as showed in the overall model of Figure 7 , we showed that NOX4 expression levels were increased in human ovarian cancer tissues, compared with the adjacent tissues, and higher expression of NOX4 was associated with poor survival and progression of ovarian cancer. Interestingly, this study showed that HIF-1α directly regulated NOX4 expression, which is consistent with the previous report that NOX4 was induced by hypoxia [ 20 , 21 ]. NOX4 was reported to produce different isoforms by cutting off exons containing NAD(P)H/FADH binding regions.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, as showed in the overall model of Figure 7 , we showed that NOX4 expression levels were increased in human ovarian cancer tissues, compared with the adjacent tissues, and higher expression of NOX4 was associated with poor survival and progression of ovarian cancer. Interestingly, this study showed that HIF-1α directly regulated NOX4 expression, which is consistent with the previous report that NOX4 was induced by hypoxia [ 20 , 21 ]. NOX4 was reported to produce different isoforms by cutting off exons containing NAD(P)H/FADH binding regions.…”
Section: Discussionsupporting
confidence: 93%
“…PTEN is a key upstream of the PI3K/Akt signaling pathway (36,38) and activated PI3K/Akt signaling contributes to cell growth and apoptosis in a number of tumors, including MM (37). In MM, PI3K/Akt is constitutively active and contributes to the the proliferation of MM cells, which suggests that the inhibition of this pathway may be a potential therapeutic approach for MM (39)(40)(41)(42). Jiang et al demonstrated that miR-20a inhibited the proliferation, migration and apoptosis of MM cells, and that these effects were associated with PI3K/AKT signaling pathway inactivation (37).…”
Section: Discussionmentioning
confidence: 99%
“…As perifosine is an Akt inhibitor, there is evidence that perifosine impedes glycolysis and therefore improve chemosensitivity in non-small lung cancer cells (50). In a recently published study of human NB cells (SH-SY-5Y), researchers found that silencing of NADPH oxidase 4 inhibited glycolysis, and this was enhanced when combined with perifosine reversing hypoxia induced chemo-resistance (51). However, the underlying mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%